Как из данной формулы выразить 'tк'? формула: c1m1(tк-t1)+c2m2(tк-t1)=с3m3(t2-tк) объясните.

lno15 lno15    2   12.06.2019 19:30    2

Ответы
missiselllэльмир missiselllэльмир  10.07.2020 07:25
Ну я попробую, что получится, то получится. 

c_{1}m_{1} (tk- t_{1}) + c_{2}m_{2} (tk-t_{1}) = c_{3}m_{3} (t_{2} - tk)

(tk-t_{1}) (c_{1}m_{1} + c_{2}m_{2}) = - c_{3}m_{3} (tk-t_{2})

 (tk-t_{1})/(tk-t_{2}) = (c_{1}m_{1} + c_{2}m_{2}) / - c_{3}m_{3}

Как-то так
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Физика